Der Bericht des Minoïdes Mynas über die Bibliothek des Klosters des hl. Ioannes Prodromos tu Bazelonos - Stefec, Rudolf S. (Byzantinische Zeitschrift, 2021)
The short catalogue of the manuscripts of the monastery of St. John the Forerunner tu Bazelonos written by Minoïdes Mynas (Par. suppl. gr. 1248, ff. 187v- 190v) in February 1845 is edited and the entries (19) matched with the only other known catalogue penned by A. Papadopulos-Kerameus in 1909 (40 entries), based on a visit to the monastery in 1884. Two of the manuscripts contained in the catalogue of Mynas can be identified (Par. suppl. gr. 613; Petropolit. BPG 743); the rest is probably lost. An inscription contained in manuscript nr. 39 of the monastery and transcribed by Papadopulos-Kerameus identifies Manuel I. Komnenos as the founder of the convent.